2021
DOI: 10.15585/mmwr.mm7016a2
|View full text |Cite
|
Sign up to set email alerts
|

Airport Traveler Testing Program for SARS-CoV-2 — Alaska, June–November 2020

Abstract: Travel can facilitate SARS-CoV-2 introduction. To reduce introduction of SARS-CoV-2 infections, the state of Alaska implemented a program on June 6, 2020, for arriving air, sea, and road travelers that required either molecular testing for SARS-CoV-2, the virus that causes COVID-19, or a 14-day self-quarantine after arrival. The Alaska Department of Health and Social Services (DHSS) used weekly standardized reports submitted by 10 participating Alaska airports to evaluate air traveler choices to undergo testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…One study in Alaska identified 951 asymptomatic travellers with positive SARS-CoV-2 test results and another two studies from Canada identified around 1–2% of asymptomatic travellers as being positive on arrival. 1 Other studies have focused on the analysis of SARS-CoV-2 infection prevalence in repatriation flights, 2–4 offering figures ranging from 0.44 to 6.3%. These figures led to some of the authors to recommend the implementation of pre-departure testing.…”
mentioning
confidence: 99%
“…One study in Alaska identified 951 asymptomatic travellers with positive SARS-CoV-2 test results and another two studies from Canada identified around 1–2% of asymptomatic travellers as being positive on arrival. 1 Other studies have focused on the analysis of SARS-CoV-2 infection prevalence in repatriation flights, 2–4 offering figures ranging from 0.44 to 6.3%. These figures led to some of the authors to recommend the implementation of pre-departure testing.…”
mentioning
confidence: 99%
“…Observed infection prevalence at arrival in French Polynesia was consistent with broad ranges observed in other, smaller-scale studies. Among arrivals into Alaska from June to November 2020, 0.8% were positive [12]; Infection prevalence at arrival was 1.0% in Toronto, Canada during September and October 2020 [14] and 1.5% in Alberta, Canada in November 2020 [13]. However, travellers in these studies did not have their country of origin reported, or information on departure testing protocol, limiting the ability of these datasets to provide comparable information on likely prevalence in countries of departure.…”
Section: Discussionmentioning
confidence: 99%
“…Countries have predominately used travel testing as a method of control, with positive individuals having to isolate, as well as being prevented from travelling at all if they test positive before departure. Although some countries with strict restrictions on traveller numbers have reported the number of arriving infections detected over time [11] and data have been reported from brief or small-scale testing programmes [12][13][14], there has been little systematic long-term data available for global travel testing. Tests have been conducted by different companies and agencies, and in combinations that can include both departure and arrival testing, typically without collation of these tests in consistent databases.…”
Section: Introductionmentioning
confidence: 99%
“…The updated search identified nine modelling studies (7)(8)(9)(10)(11)(12)(13)(14)(15) and eight observational studies (16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Study Designsmentioning
confidence: 99%
“…Five observational studies assessing the impact of microbiological detection only on this outcome (17,19,(21)(22)(23) reported detecting from 0.01% to 1.5% of cases amongst all travellers. Self-collection of samples was conducted at 4 days post-arrival (17).…”
Section: A Proportion Of Cases Detectedmentioning
confidence: 99%